Asuhan Keperawatan Jiwa Pada Pasien Dengan Halusinasi Pendengaran Di Wisma Flamboyan Rsj. Dr. Prof. Hb Saanin Padang - Aisyah Putri Zalita; Ramaita .; Dwi Happy Anggia Sari; Vivi Yuderna (CV. ITTC INDONESIA, 2026)
Hallucinations are a form of perceptual disorder, a condition where a person experiences sensory stimulation without any real stimulus from the surrounding environment. Based on medical record data from RSJ Based on medical record data from RSJ Prof. HB. Saanin Padang, hallucinations have become the most common nursing diagnosis in the last 3 year (2023-2025) with a total of 17,591 clients Prof. HB. Saanin Padang. When hallucinations occur, individuals often feel very anxious, panicked, and have difficulty distinguishing between what they imagine and the reality they are experiencing. This study aims to describe the application of psychiatric nursing care to patients with auditory and visual hallucinations at Wisma Flamboyan. The method used was a case study with a nursing process approach that includes assessment, diagnosis, planning, implementation, and evaluation. The results of the assessment showed that the client experienced signs and symptoms of hallucinations in the form of hearing whispers and seeing shadows that were not there. The main nursing diagnosis was hallucinations with a co-diagnosis of self-care deficit. After being given nursing care, the client was able to control his hallucinations by implementing hallucination implementation strategies, namely SP 1-4. These results indicate that SP implementation is effective in helping clients control hallucinations. Self Care Deficit diagnoses can also be addressed with implementation strategies (SP), namely 1-4. This research is expected to increase public understanding and awareness of the importance of maintaining mental health to achieve optimal mental well-being.